Comparison of software complexity metrics in measuring the complexity of event sequences - Ahmad, Johanna; Baharom, Salmi (Springer, 2017)
One of the main challenges in software development is the complex structure of a system. The software development for event sequences is complex. It is a challenge to define a complexity metric for event sequences application. Lack of knowledge in complexity metric can lead to issues such as rises in software cost and delays in project timing. Numerous complexity metrics have been proposed and published, such as information flow complexity, lines of code, function points, and unique complexity metric. However, in the context of the event sequences, most of the research focuses on measuring web graphs, measuring the web traffic and how the complexity of the web impacts the customer. In this paper, the researchers studied and compared five different software complexity metrics. This paper describes the on-going research that addresses the issue to produce a unique weight to prioritise event sequences test cases.